MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN METODE DEMONSTRASI DALAM PENINGKATAN HASIL BELAJAR PPKN KELAS X TATA BUSANA DI SMK MUHAMMADIYAH 5 PURWANTORO KAB. WONOGIRI - Jatmiko, Wahyu; Sunari, Sunari; Triyono, Triyono (EDUPEDIA, 2023)
This study aims to improve civics learning outcomes through a problem-based learning model in class X students concentrating on Fashion Design (TB 1) at SMK Muhammadiyah 5 Purwantoro in the 2022/2023 academic year. The subjects in this study were students in class X concentration on dressmaking skills (TB 1) in the odd semester of the 2022/2023 academic year, totaling 33 students, all of whom were female as the subjects receiving the action, while the subject of the action was the PPKn teacher class X Fashion Design (TB 1) namely as a researcher who observes the learning process. Methods of data collection is done through test techniques, observation and documentation. This action research was conducted in two cycles, each cycle consisting of: planning, action, observation and reflection. The use of the problem-based learning learning model with the demonstration method can improve PPKn learning outcomes for Class X students of Class X Fashion Design (TB 1) at Muhammadiyah Vocational School 5 Purwantoro in the 2022/2023 academic year. This can be seen from the average value of PPkn learning outcomes of students who also experienced an increase, namely before the action of 70.43 in the first cycle of 75.48 and in the second cycle of 77.59. In addition, the percentage of student learning completeness, namely before the action was 27%, in cycle I was 64% and in cycle II was 85%.